Pengaruh Celebrity Endorsement dan Citra Merek terhadap Niat Beli Kopi Caffino melalui Sikap terhadap Merek - Darmawan, Mirza Dwi; Iriani, Sri Setyo (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The increasing level of competition in marketing requires companies to present different marketing strategies that are superior to competing companies. Caffino is a local coffee brand from Indonesia that using celebrity endorsement as marketing strategies to enhance customer purchase intention. The purpose of this paper is to analyze and discuss the effect of celebrity endorsement and brand image on purchase intention through the attitude toward brand on Caffino coffee. This type of research is quantitative research. This research uses a non-probability sampling technique. Questionnaires were distributed to 200 participants with Google form. Data analysis techniques using path analysis. The results of this study showed that there is a positive and significant effect of celebrity endorsement and attitude toward brand on purchase intention. However, the brand image had no significant effect on purchase intention. There is also a positive and significant effect of celebrity endorsement and brand image on attitude toward the brand.